Draft Genome Sequence of the Putative Endophytic Bacterium Pantoea agglomerans R6, Associated with Lactuca serriola from South Africa - Istain, Brandon (Microbiol Resour Announc, 2021)
Here, we present the draft genome sequence (∼4.7 Mb) of the endopyhtic bacterium Pantoea agglomerans strain R6, which was isolated from surface-sterilized roots of Lactuca serriola (prickly lettuce).